Site leaching model and climate change impacts of an expanding coastal dumpsite - Wang, Yijie (Nanyang Technological University, 2024)
Coastal dumpsites, historically common in low-lying estuarine and coastal areas, pose significant pollution risks due to their unlined nature and lack of leachate management. These sites are uncontrolled and vulnerable to erosion and flooding, especially with anticipated climate change impacts. The leachate from these dumpsites, often laden with heavy metals and organic pollutants, significantly threatens surrounding soil and groundwater systems. Few studies have examined historical leaching during dumpsite expansion and future climate change impacts. To address this, we conducted a case study of the Thilafushi dumpsite in the Maldives. A simple yet universal coupled model, incorporating geometric modeling, Hydrologic Evaluation of Landfill Performance (HELP) Model version 4.0, and numerical models is proposed and validated by site monitoring data. This study provides a novel solution for modelling both dimensions and leaching patterns for an expanding dumpsite, while pioneering quantitative consideration of future climate change impacts. The results show that the historical cumulative release of Dissolved Organic Carbon (DOC), Cu, and Cr exhibits an increasing trend, which is likely to continue in the future. Simulations indicate that from 2022 to 2050 and 2100, the cumulative release of contaminants could increase by up to 100% and 200%, respectively. Among the climate change impacts analyzed, temperature rise significantly contributes to increased contaminant leaching, while rainfall and sea-level rise have minimal impact. This is due to the small variation on cumulative rainfall and the small change in sea level rise during a long period of time. The combined effect of temperature and precipitation is projected to lead to the cumulative release of Cu to rise by up to 23% under extreme conditions compared to the baseline scenario. This research addresses gaps in quantitative methods for leachate production and transport in expanding dumpsites, focusing on climate change impacts. It also seeks to provide insights into historical and future leaching trends in coastal dumpsites.